Tocols and oil content in whole grain, brewer's spent grain, and pearling fractions of malting, feed, and food barley genotypes. Issue 6 (5th September 2018) - Badea, Ana; Carter, Adam; Legge, William G.; Swallow, Kevin; Johnston, Stuart P.; Izydorczyk, Marta S.
Abstract: Background and objectives: Vitamin E is an important dietary component found mainly in plants and is a group of compounds including tocopherols and tocotrienols, collectively known as tocols. In this study, tocols and oil content was evaluated in whole grain, brewer's spent grain, and pearling fractions from various barley genotypes grown at two sites in 2014, and at three sites in 2015 in Manitoba, Canada. Findings: Mean tocols and oil content was much higher in brewer's spent grain than in whole grain of malting genotypes. Pearling fractions had higher tocols and oil content than whole grain of six distinct feed/food genotypes, with the highest tocols and oil content observed in the 5%–10% pearling fraction. Conclusions: Brewer's spent grain and the 5%–10% pearling fraction could be used as novel functional food ingredients or be valuable sources for extraction of health‐promoting tocols and/or oil. Significance and novelty: Using barley processing by‐products like brewer's spent grain and pearling fractions in value‐added products with beneficial health properties may offer unique economic and waste management opportunities. A relatively large number of malting and feed/food barley genotypes were screened for all eight tocol vitamers and oil content. This study serves as a valuable resource for barley research scientists and the barley industry as a whole.